Determinan Kapabilitas Kurator terhadap Kinerja Kurator melalui Kepuasan Kerja yang Dimoderasi Komitmen pada Kurasi UMKM Jawa Timur - Rinawati, Liya; Eddy Yunus; Slamet Riyadi (Jurnal Riset Akuntansi, 2026)
This study is motivated by the significant role of Micro, Small, and Medium Enterprises (MSMEs) in the national economy, particularly in generating employment and supporting economic growth, while still facing challenges related to product quality and competitiveness. In this context, product curation emerges as a strategic mechanism to enhance quality standards and market readiness, making the role of curators increasingly important. This study aims to analyze the influence of curator competence, digital curation technology, work environment, work motivation, work targets, teamwork, and personality traits on job satisfaction and curator performance in MSMEs, as well as to examine the role of job satisfaction as a mediating variable and commitment as a moderating variable. The research employs a quantitative approach with an explanatory design, using primary data collected through questionnaires distributed to 251 curators affiliated with the East Java Curation House. Data analysis was conducted using multiple linear regression, along with mediation and moderation testing. The findings indicate that curator competence, digital curation technology, work targets, teamwork, and job satisfaction have a significant effect on curator performance, while job satisfaction also mediates several relationships among variables. However, curator commitment does not act as a moderating variable. The implications of this study highlight the importance of strengthening curator competence, enhancing the utilization of digital technology, and developing structured and collaborative work systems to improve curator performance and the sustainable competitiveness of MSMEs.